Peran Tokoh Adat dalam Pembentukan Desa di Kecamatan Ukui Kabupaten Pelalawan - Artina, Dessy; naidi, Jun (Melayunesia Law, 2017)
AbstractÂ Indigenous leaders play a role in fostering and controlling the attitudes and behavior of the society to conform with the provisions of customs, as well as during conflicts or disputes caused by the separation of the village. Village formation is formed on the initiative of the society by taking into account the origin of the village and the socio-cultural conditions of the local society. This study aims to find out how the role of customary figure in formation in Ukui, Pelalawan District. Discusses the boundaries of the territory in charge of organizing and managing the interests of the local society based on local origins and customs that are recognized and respected in the governance system and the non-involvement of the Batin within in the expansion area,whether in asking for views or in asking for opinions as persons know about ulayat lands and village boundaries.AbstrakÂ Tokoh adat berperan dalam membina dan mengendalikan sikap dan tingkah laku warga masyarakat agar sesuai dengan ketentuan adat termasuk juga disaat terjadi konflik atau perselisihan yang disebabkan pemekaran desa. Pembentukan Desa dibentuk atas prakarsa masyarakat dengan memperhatikan asal-usul desa dan kondisi sosial budaya masyarakat setempat. Penelitian ini bertujuan untuk mengetahui bagaimana Peran Tokoh Adat dalam Pembentukan Di Kecamatan Ukui Kabupaten Pelalawan. Membahas batas wilayah yang berwenang untuk mengatur dan mengurus kepentingan masyarakat setempat berdasarkan asal usul dan adat istiadat setempat yang diakui dan dihormati dalam sistem pemerintahan dan tidak dilibatkannya para Batin yang ada didalam Wilayah Pemekaran tersebut, baik dalam meminta pandangan ataupun dalam meminta pendapat sebagai orang yang tahu tentang tanah ulayat dan batas wilayah desa.